Severity of scleroderma lung disease is related to alveolar concentration of nitric oxide - Tiev, K P; Cabane, J; Aubourg, F; Kettaneh, A; Ziani, M; Mouthon, L; Duong-Quy, S; Fajac, I; Guillevin, L; Dinh-Xuan, A T (The European respiratory journal, 2007)
The alveolar concentration of exhaled nitric oxide (CA,(NO)) is increased in patients with systemic sclerosis (SSc), but whether this increase is related to the severity of interstitial lung disease (ILD) in SSc has not yet been investigated. In total, 58 SSc patients prospectively underwent pulmonary function tests (PFTs), echocardiogram and fibrosis scoring on pulmonary computed tomography (CT). Patients were divided into two groups according to the presence (or not) of ILD. Measurements of CA,(NO) were assessed in all SSc patients and compared with those obtained in 19 healthy volunteers. Relationships were sought between CA,(NO) PFTs and CT scan fibrosis scores. Overall, CA,(NO) was significantly increased in SSc patients (median (range) 6.2 (3.8-9.9) ppb) as compared with controls (2.0 (1.2-3.0) ppb). Among SSc patients, CA,(NO) was significantly higher in patients with ILD compared with patients without ILD (n = 33, 7.5 (5.2-11.9) ppb versus n = 25, 4.9 (3.1-7.0) ppb, respectively). CA,(NO) was inversely related to total lung capacity (r = -0.34) and the diffusing capacity of the lung for carbon monoxide (r = -0.37) and was directly related to CT scan fibrosis scores (r = 0.36). An increased alveolar concentration of exhaled nitric oxide could, at least in part, either reflect or contribute to the severity of lung disease and could be used to noninvasively assess the extent of interstitial lung disease in systemic sclerosis.